2017
DOI: 10.1007/s00127-017-1365-1
|View full text |Cite
|
Sign up to set email alerts
|

Experience of stigma in the public life of relatives of people diagnosed with schizophrenia in the Republic of Belarus

Abstract: With respect to the public domain of life, substantial stigma and discrimination perceived by families of people living with schizophrenia in Belarus is associated with structural issues of the country's mental health care system. To reduce the stigma-related burden, action must be taken to: (1) educate and support families and (2) deal with structural issues, by reorganising mental health services to better meet the needs of the families of people diagnosed with schizophrenia, and by including them in decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 51 publications
0
20
0
3
Order By: Relevance
“…The majority of the studies (researches from USA, Germany, Canada, Spain, Italy, Iran, Dutch, Belarus, and Czech Republic) in this review showed that in addition to the inadequacy of mental health care, participants reported experiencing negative attitudes or discriminatory responses in their contacts with mental health professionals (Angermeyer et al ; Atine ; Buizza et al ; Gonzalez‐Torres et al ; Krupchanka et al, ; Krupchanka et al, ; Krupchanka et al ; O'Grady ; van der Sanden et al ; Shamsaei et al ), and one study from Israel even made this the main topic of its research (Amsalem et al ).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The majority of the studies (researches from USA, Germany, Canada, Spain, Italy, Iran, Dutch, Belarus, and Czech Republic) in this review showed that in addition to the inadequacy of mental health care, participants reported experiencing negative attitudes or discriminatory responses in their contacts with mental health professionals (Angermeyer et al ; Atine ; Buizza et al ; Gonzalez‐Torres et al ; Krupchanka et al, ; Krupchanka et al, ; Krupchanka et al ; O'Grady ; van der Sanden et al ; Shamsaei et al ), and one study from Israel even made this the main topic of its research (Amsalem et al ).…”
Section: Resultsmentioning
confidence: 91%
“…Several studies (researches from USA, Germany, Italy, Belarus, India, and Czech Republic) discussed structural discrimination due to a perceived inadequacy of medical support, information (regarding illness, treatment, and service), and the lack of legislation applicable to people with mental illness and their family members (Angermeyer et al ; Atine ; Buizza et al ; Koschorke et al, ; Krupchanka et al, ; Krupchanka et al, ; Krupchanka et al ; Muhlbauer ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations